Yigael Yadin Finds a Bama at Beer-Sheva - Shanks, Hershel (The Biblical archaeology review, 1977)
On my last visit to Jerusalem, I stopped in to see Yigael Yadin—as I always do. It was a fascinating hour—as it always is.